A Review of Biosensors; Definition, Classification, Properties, and Applications - Noori, Husham. N.; Abdulameer, Ameer F. (Iraqi Journal of Science, 2023)
Biosensor is defined as a device that transforms the interactions between bioreceptors and analytes into a logical signal proportional to the reactants' concentration. Biosensors have different applications that aim primarily to detect diseases, medicines, food safety, the proportion of toxins in water, and other applications that ensure the safety and health of the organism. The main challenge of biosensors is represented in the difficulty of obtaining sensors with accuracy, specific sensitivity, and repeatability for each use of the patient so that they give reliable results. The rapid diversification in biosensors is due to the accuracy of the techniques and materials used in the manufacturing process and the interrelationships in scientific research between various disciplines, i.e., physics and biology, engineering and biology. This research aims to define biosensors in general, classify them and show their most important applications, with a brief description of their time development and the reason for their speared in all fields.